2020
DOI: 10.3390/w12113196
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Removal and Dynamics of Microbial Community of A Hydrogen-Based Membrane Biofilm Reactor at Diverse Nitrate Loadings and Distances from Hydrogen Supply End

Abstract: The back-diffusion of inactive gases severely inhibits the hydrogen (H2) delivery rate of the close-end operated hydrogen-based membrane biofilm reactor (H2-based MBfR). Nevertheless, less is known about the response of microbial communities in H2-based MBfR to the impact of the gases’ back-diffusion. In this research, the denitrification performance and microbial dynamics were studied in a H2-based MBfR operated at close-end mode with a fixed H2 pressure of 0.04 MPa and fed with nitrate (NO3−) containing infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…The population of Hydrogenophaga exhibited low relative abundances in our study compared with previous work [42,43]. The possible explanations for the lack of Hydrogenophaga in the present study are as follows: (1) the successful PN-D process brings about the accumulation of NO − 2 in the MBR effluent; the presence of NO − 2 has a toxic effect on Hydrogenophaga, and the reproduction of Hydrogenophaga is sensitive to its presence [17]. (2) The MBfR influent contained synthetic wastewater and domestic wastewater with COD, NO − 3 , and NO − 2 , and other nitrogen compounds.…”
Section: Microbial Community Analysis In Different Phases Of Mbr-mbfrcontrasting
confidence: 64%
See 1 more Smart Citation
“…The population of Hydrogenophaga exhibited low relative abundances in our study compared with previous work [42,43]. The possible explanations for the lack of Hydrogenophaga in the present study are as follows: (1) the successful PN-D process brings about the accumulation of NO − 2 in the MBR effluent; the presence of NO − 2 has a toxic effect on Hydrogenophaga, and the reproduction of Hydrogenophaga is sensitive to its presence [17]. (2) The MBfR influent contained synthetic wastewater and domestic wastewater with COD, NO − 3 , and NO − 2 , and other nitrogen compounds.…”
Section: Microbial Community Analysis In Different Phases Of Mbr-mbfrcontrasting
confidence: 64%
“…Here, nitrate and nitrite diffuse from water into biofilm being reduced [14,15]. The advantages of this hydrogenotrophic denitrification compared with conventional heterotrophic denitrification technology include the utilization of nontoxic and inexpensive H 2 as electron donors, no requirement for the addition of external organic carbon, a small footprint, relatively low cost, and low production of biological sludge [16,17]. Promising outcomes have been reported with MBfR for treating nitrate-and nitrite-contaminated water for research and commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas is a hydrogen autotrophic denitrifier and a nitrate-reducing taxa that has been shown to play a key role in hydrogen autotrophic denitrification during removal ( Zhang et al, 2015 ). Hydrogenophaga is a well-known, but uncultured, hydrogen-oxidizing bacterial genus that characteristically reduces and can play a large role in H 2 -based MBfR functioning ( Jiang et al, 2020 ). In addition, Thauera have been previously considered the most active denitrifying bacteria in sewage treatment systems, and were the primary contributor to nitrogen wastewater denitrification in a previous study ( Dong et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the sealed gas supply mode of the H 2based MBfR, the diffusion flux of the effective gas at the end of the HFM to the biofilm is usually low, which can prevent many fiber membranes from operating and decreasing the utilization efficiency, ensuing in the waste of the membrane material and reactor volume. Jiang et al (2020) also showed that most of the functional genes associated with the microbial metabolism and denitrification processes in microbial communities on HFM in closed operation mode showed a weakening trend as they moved away from the gas supply side, under the influence of gas counter-diffusion. Therefore, this back-diffusion reduced the total effectiveness of the biofilm and the average denitrification efficiency.…”
Section: Introductionmentioning
confidence: 93%